Impacts of Permafrost Degradation on Hydrology and Vegetation in the Source Area of the Yellow River on Northeastern Qinghai-Tibet Plateau, Southwest China - Jin, Xiaoying; Jin, Huijun; Luo, Dongliang; Sheng, Yu; Wu, Qingbai; Wu, Jichun; Wang, Wenhui; Huang, Shuai; Li, Xiaoying; Liang, Sihai; Wang, Qingfeng; He, Ruixia; et al. (Frontiers in Earth Science, 2022)
Under a persistent warming climate and increasing human activities, permafrost in the Source Area of the Yellow River (SAYR) has been degrading regionally, resulting in many eco-environmental problems. This paper reviews the changes in air temperature and precipitation over the past 60 years and presents the distribution and degradation of alpine permafrost in the SAYR. The review is focused on the permafrost degradation–induced changes in hydrology, wetlands, thermokarst lakes, ponds, and vegetation. Mean annual air temperatures have been rising at an average rate of 0.4°C/10a over the past 60 years, while precipitation has increased only slightly (16 mm/10a). Borehole temperature monitoring at the depth of 15 m shows the permafrost warming rates of 0.01–0.21°C/10a in the Headwater Aera of the Yellow River. As a result of permafrost thaw, the amount of surface waters has declined while groundwater storage has increased. Due to permafrost degradation, the supra-permafrost water table lowers gradually, resulting in a reduction in areal extents of wetlands and lakes in the SAYR. We further renamed the concept of the burial depth of the ecologically-safe supra-permafrost water table, the minimum depth of the groundwater table for sustaining the normal growth of alpine grassland vegetation, for the SAYR to describe the relationship between the lowering permafrost table and succeeding alpine vegetation. Furthermore, we recommended more studies focusing on snow cover and carbon stock and emissions related to permafrost degradation under a warming climate. We also advised to timely establish the long-term monitoring networks for the rapidly changing mountain cryosphere, alpine ecology, alpine hydrology, eco-hydrology, cryo-hydrogeology, and carbon fluxes. Moreover, process-based models should be developed and improved to better simulate and predict the responses of alpine ecosystem changes to the interacting cryospheric and other environmental variables and their ecological and ecohydrological impacts in the SAYR and downstream Yellow River basins. This study can help better manage the ecological and hydrological environments in the Upper Yellow River that are sensitive to changes in the alpine climate and cryosphere.